左边=∫[0,x] (2t^2+2t|t|) dt
t>=0时,∫ t|t| dt= ∫ t^2 dt= t^3/3 + C = |t|t^2 / 3 + C,
t<0时,∫ t|t| dt = -∫ t^2 dt = -t^3/3 + C = |t| t^2 / 3 + C
所以原式=(2t^3/3 + 2|t| t^2 / 3) |[0,x] = (2t^2/3 * (t + |t|)) |[0,x] = 2x^2/3 * (x+|x|)
∫[a,b] f(t) f'(t) dt = ∫[a,b] f(t) df(t) = (分部积分) =(f(t) * f(t)) |[a,b] - ∫[a,b] f(t) df(t)
所以2∫[a,b] f(t) df(t) = (f(b))^2 - (f(a))^2,所以左边=[(f(b))^2 - (f(a))^2] / 2
令x^2+1=2得:x=±1,令x^2+x=2得:x=1或者x=-2
注意到x^2+x不总是大于0,令x^2+x=0,得x=0或者x=-1
所以S=∫[-2,-1] (x^2+x) dx + ∫[0,1] (x^2+x) dx - ∫[-1,0] (x^2+x) dx - (2 * 2 - ∫[-1,1] (x^2+1) dx)
=1/2